Penilaian Proyek Penguatan Profil Pelajar Pancasila Pada Kurikulum Merdeka - Zulpan; Arianto; Ahmad Husein; Sahrul Sahrul; Fitria Wahyu Nugraheni; Abdullah (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
This article aims to describe the concept of Pancasila Student Profile Enhancement Project Assessment (P5). The method of writing an article uses descriptive qualitative analysis based on references from textbooks, guidebooks, and relevant scientific articles. The results of this study are a concept about the assessment of P5, starting from before, during, and after the P5 learning activities. This article is expected to facilitate educators in implementing assessments in the Project to Strengthen the Pancasila Student Profile learning, thus becoming a credible scientific source. The Pancasila Student Profile consists of a set of characters and competencies that are intended to be achieved by students, based on the noble values of Pancasila. The purpose of translating funds is to convey the goals and vision of education into a format that is more easily understood by all stakeholders in education, with the ultimate aim of aligning all learning, programs, and activities within the educational unit. Guidelines for the Development of the Pancasila Student Profile Strengthening Project along with the guidebook on the Dimensions, Elements, and Sub-elements of the Pancasila Student Profile established by the Ministry of Education, Culture, Research, and Technology. Four criteria have been classified in the P5 Report: beginning to develop, developing, developing as expected, and highly developed.